Volatile and phenolic profiles of traditional Romanian apple brandy after rapid ageing with different wood chips. (1st August 2020) - Coldea, Teodora Emilia; Socaciu, Carmen; Mudura, Elena; Socaci, Sonia Ancuţa; Ranga, Floricuţa; Pop, Carmen Rodica; Vriesekoop, Frank; Pasqualone, Antonella
Highlights: Pălinca is a traditional double batch-distilled Romanian fruit brandy. Rapid ageing of pălinca impacts both the volatile and phenolic profiles regardless of the wood types employed. Fir and cherry wood contributed the largest quantity of phenolic compounds to pălinca. The lowest contribution to volatile profile of pălinca was given by the mulberry wood. The esters of fatty acids contributed the most to the volatile profile of pălinca . Abstract: The aim of this work was to find differences in the volatile and phenolic profiles of the traditional Romanian apple brandy pălinca aged with various species of wood chips. Seven types of wood species, two types of oak ( Quercus petraea and Quercus robur ), plus sweet chestnut, mulberry, walnut, fir and cherry, were considered. The majority of volatile compounds characterizing the aroma profile of pălinca were esters, particularly ethyl esters, with ethyl isobutyrate, ethyl isovalerate, ethyl caproate, ethyl octanoate and ethyl decanoate as the most abundant. The most important source of catechin was cherry wood. Rutin and juglone were solubilised only in walnut wood aged brandy. Vanillin, increased significantly in chestnut aged apple brandy. Given the cost and difficulty in handling wooden barrels, and as an alternative being able to select from a range of specific wooden chips, this work could potentially guide actors in beverage industry to less expensive alternatives.